Generation of a control iPS cell line (JUCGRMi006-A) with no abnormalities in Parkinson's disease-related genes - Kei-ichi Ishikawa; Takahiro Shiga; Manabu Funayama; Nobutaka Hattori; Wado Akamatsu (Stem Cell Research, 2024)
The appropriate control of induced pluripotent stem cells (iPSCs) is essential for studying iPSCs derived from patients with Parkinson’s disease (PD). Here, we established an iPSC line from a healthy female donor. The iPSCs were pluripotent, could differentiate into three germ layers, and had normal karyotypes. We also confirmed that the iPSC line exhibited no PD-related gene abnormalities. This iPSC line will be useful for PD research.